Field Response to Pustule Bacteria and Yield of Several Soybean Varieties in the Mahogany Agroforestry System Under El Niño Dry Season in 2023 - Haqiki, Zahra Tazkiyatun; Hadiwiyono, Hadiwiyono; Poromarto, Susilo Hambeg (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
The factors that affect the low national soybean production are the reduction of agricultural land, the dry season, and extreme temperatures due to El Niño. Agroforestry can be one of the solutions, but the environmental conditions that make soybean plant growth less suitable can make it vulnerable to pathogens causing disease, such as a bacterial pustule caused by Xanthomonas axonopodis pv. glycines. This research aimed to evaluate the field response to bacterial pustules and the yield potential of various soybean varieties in mahogany agroforestry systems under the stress of the 2023 El Niño drought. This research was carried out during the El Niño dry season, August-October 2023, in the Alas Bromo Special Purpose Forest Area, Karanganyar District, Karanganyar Regency, Central Java. The research design used in this research was a complete randomized design with the factor of soybean varieties using six varieties planted under mahogany tree stands. The observed variables were height, the number of leaves, disease incidence, disease severity, infection rate, and area under the disease progression curve (AUDPC). The result showed that two varieties resistant to bacterial pustule: Agromulyo and Denasa-2. El Niño, dry season stress, causes low yield productivity; the highest yield was just 0.6 t/ha, produced by the Argomulyo variety.